Breaking Barriers and Nurturing Acceptance: Exploring School Teachers' Knowledge and Awareness About LGBTQ+ Communities (GAIMS Journal of Medical Sciences, 2024)
Background: LGBTQ+ communities are constantly facing disparities related to social stigma and denial of human rights. Among youth, the formative years of upper primary and high school are pivotal for self-discovery. School teachers have a key role in creating a supportive environment for LGBTQ+ students. This study aims to explore the level of knowledge and awareness among school teachers regarding LGBTQ+ communities and their rights, with the ultimate goal of developing strategies to improve teacher education and support for LGBTQ+ students.Materials and Methods: A cross-sectional study was conducted among 255 school teachers aged 23 to 60 years from 17 schools in Thrissur district in Kerala, India, based on convenient sampling techniques. A semi-validated questionnaire was distributed among school teachers of high school and upper primary classes. Based on the scores obtained they were categorized as good, average and poor. Chi-square test was used for the analysis.Results: Out of the total respondents, 56.5% exhibited average knowledge, while 53.7% showed poor awareness. Notably, a statistically significant finding emerged, indicating a paradoxical scenario where a majority possessed commendable knowledge, yet concurrently showcased a significantly poor level of awareness (p value= 0.002). Specifically, as age increased, there was aconcurrent decrease in both knowledge and awareness levels. Subgroup analysis delineated a statistically significant distinction, with the younger age groups (< 40 years) manifesting higher levels of knowledge compared to their older counterparts (> 51 years) (p value= 0.013).Conclusions: This study highlights the lack of LGBTQ+ knowledge and awareness among teachers. Introducing Comprehensive Sexuality Education in schools is crucial for a safe environment enhancing LGBTQ+ youth's well-being and academic outcomes. It is our collective responsibility to ensure all students feel seen, heard, and valued, irrespective of sexual orientation or gender identity.